RANCANG BANGUN APLIKASI PENGADUAN MASYARAKAT BERBASIS ANDROID - PARMONANGAN ROTUA TOGATOROP; NITA SIRAIT; EVI FANY SIDABUTAR; ROMMEL GULTOM (LP2MTBM MAKARIOZ, 2021)
This study aims to produce a public complaint application that can be used by the public in conveying their aspirationsregarding problems that occur in the midst of the community. This application is built on a smartphone system with the Androidoperating system that can be used by the public in daily communication related to submitting complaints. In this research, themethod used is the Software Development Life Cycle (SDLC) method, which is a systematic development model, design, andmaintenance of software projects that ensure all user needs are met. This application is built using the Java programminglanguage. This application will display the types of complaints, the date of the complaint, the user who made the complaint andthe status of the complaint. Based on the results of interviews conducted with the public, it shows that this application willreally help the community in making complaints.